2004
DOI: 10.1038/sj.bjc.6601997
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide in paediatric high-grade glioma: a key for combination therapy?

Abstract: This report describes a single-centre study with temozolomide (TMZ) (200 mg m À2 day À1 Â 5 per cycle of 28 days) in children with (recurrent) high-grade glioma. Magnetic resonance imaging was performed every two cycles. In all, 20 patients were treated between 1998 and 2001 after the UKCCSG/SFOP TMZ phase II trial. All patients had measurable disease. Totally, 15 patients had a relapse after surgery7radiotherapy7chemotherapy. Overall, five patients received TMZ after surgery or biopsy, awaiting radiotherapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 26 publications
1
12
1
Order By: Relevance
“…Verschuur et al treated 20 children with recurrent high-grade gliomas, including 11 grade III and 8 grade IV gliomas. Progression-free survival at 6 months was 18 and 12.5% for each grade (5). Those figures are less favorably compared to those reported in adult studies (1,2).…”
Section: Introductioncontrasting
confidence: 49%
“…Verschuur et al treated 20 children with recurrent high-grade gliomas, including 11 grade III and 8 grade IV gliomas. Progression-free survival at 6 months was 18 and 12.5% for each grade (5). Those figures are less favorably compared to those reported in adult studies (1,2).…”
Section: Introductioncontrasting
confidence: 49%
“…In contrast to adult HGGs, it has been reported that pediatric HGGs have a poor response to adjuvant temozolomide and more increased side effects [2,4,9,11,20], with objective response rates of 12 and 20 % [9,20]. One study reported that there was no objective response and SD was obtained in 29 % of the patients [11].…”
Section: Discussionmentioning
confidence: 83%
“…Adverse side effects occurred in o50% of the cohort with the most common side effects consisting of bacteremia, nausea/vomiting, elevated transaminases and decreased performance, supporting previous studies citing the favorable toxicity profile of temozolomide. 9,13 On the basis of the results of this study, we conclude that increased doses of temozolomide are feasible when given with AHCR. As with many high-dose chemotherapy trials, efficacy of treatment will need to be analyzed in the context of multimodal therapy, but the combination of temozolomide, thiotepa and carboplatin with AHCR may improve survival in patients with recurrent malignant brain tumors, in particular those with highgrade gliomas in second or third complete response and those with minimal residual disease.…”
Section: Discussionmentioning
confidence: 95%
“…9 When administered daily at 200 mg/m 2 for 5 days every 28 days, temozolomide showed a tolerable toxicity profile in children, with myelosuppression being the most common side-effect reported. 9,13 The current study builds upon prior research with high-dose chemotherapy and AHCR 4,[14][15][16][17][18][19][20] with the addition of temozolomide in place of etoposide. 4,15 The primary objective of this study was to define the maximum tolerated dose (MTD) of temozolomide administered twice daily in combination with myeloablative 1 doses of thiotepa and carboplatin with AHCR in patients with either recurrent high-grade brain tumors with minimal residual disease or those with newly diagnosed brain tumors with minimal residual disease following conventional therapy.…”
Section: Introductionmentioning
confidence: 99%